FAILURE ANALYSIS OF THE COATING OF TRANSMISSION MECHANISM BASED ON COHESIVE ZONE MODEL - WANG Ning; LIU YuanQing; WANG Bo; LI WeiTuo; SUN GuoPeng (Jixie qiangdu)
Hard coatings has the advantages of good wear resistance and high contact fatigue life which has been widely used in aerospace and aviation fields. However, the coating/subtrate interference will occur delamination failure under the heavy load, and the reliability of machine parts has been affected. Recently, study on the coatings failure mechanisms and the bonding ability of coatings is greatly focused on. The article adopting cohesive zone model combined with FEM analysis the delamination failure of the coating/subtrate interference. The results show that the simulation results based on the cohesive zone model coincides with the experimen results. On this foundation, the effects of different factors on the adhesion strength of coatings are studied. The bonding strength of coatings has been greatly increased by increasing the thickness and elastic modulus of coatings, and the carrying capacity has greatly improved.